Effects of deep water and treadmill running on oxygen uptake and energy expenditure in seasonally trained cross country runners - DeMaere, J.; Ruby, B. C.; Swan, J. (Medicine & Science in Sports & Exercise, 1997)
Deep water and treadmill running at 60 and 80% VO2max were compared on a number of physiological variables. VO2 and energy expenditure were similar in both exercise modalities indicating the overall active muscle mass was quite similar. However, other variables were significantly different. Ventilation and respiratory exchange ratio were higher in deep water running suggesting that the pattern of muscular recruitment was altered particularly at the higher level of effort. Implication: Although deep water running is a popular training modality for rehabilitation and appears to elicit similar rates of energy expenditure to that of treadmill running, the concepts of training specificity have to be considered when training for running on land. Deep water running does not appear to have any added values to that which could be achieved by solely indulging in land training.